(untitled) (Iraqi Journal of Science, 2022)
The purpose of this study is the activation of natural Iraqi bentonite that has been obtained from Wadi Bashira region, in the Western Desert of Iraq, to obtain the Nano particle sized then Nano-Quartz was extracted. This method included bentonite nano particles preparation by purification with HCl solution, calcination, the planetary ball mill to get bentonite in nanometer size and centrifugation to obtain the Nano-quartz. Results of quartz purification process were characterized by Fourier transforms infrared spectroscopy (FTIR), energy dispersive X-ray spectroscopy (EDS) and scanning electron microscope (SEM), particle size analyzer (PSA) and the X-rays diffraction (XRD). All tests have shown almost a clear decline in the proportion of the high-calcium in crude Iraqi bentonite in conjunction with an increase in high rates of silica in Quartz phase.